Philosophy of dividing the Computer Science into Several fields (International Journal of Engineering and Computer Science, 2018)
There are many divisions of philosophy named the philosophy of a domain where domains going from history to physics. This essay proposes some issues that might constitute the philosophy of computer science as architecture of computer, divide the science into hardware and software, programming languages, operating systems, network architecture, security, privacy, and of protect the machine by anti-virus